Knowledge transfer from sport science to coaching: a South African coach`s perspective - Kubayi, A.; Coopoo, Y.; Toriola, A. (South African Journal for Research in Sport, Physical Education and Recreation, 2019)
This study examined the extent to which sport science knowledge translates to coaching. The sample consisted of 202 South African sport coaches (174 males; 28 females; mean age=31.56±8.85 years; coaching experience mean: 6.22±5.13 years). Data were collected using a validated questionnaire. The results showed that injury prevention and recovery, fitness/conditioning, individual skill development, training programmes (strength, endurance, etc.), tactics/strategy, nutrition and mental training and preparation were most likely to be of interest to sport coaches. Coaches reported that they were more likely to interact with other coaches, watch sport coaching videos, attend conferences/workshops, consult mentors and experiment with new ideas in order to obtain new information. This study underscores the need for coaches and sport scientists to collaborate directly in order to communicate and disseminate knowledge effectively between sport science and coaching.